The exceptional sensitivity of brain mitochondria to copper - Borchard, Sabine; Bork, Francesca; Rieder, Tamara; Eberhagen, Carola; Popper, Bastian; Lichtmannegger, Josef; Schmitt, Sabine; Adamski, Jerzy; Klingenspor, Martin; Weiss, Karl Heinz; Zischka, Hans (Toxicology in vitro, 2018)
Wilson disease (WD) is characterized by a disrupted copper homeostasis resulting in dramatically increased copper levels, mainly in liver and brain. While copper damage to mitochondria is an established feature in WD livers, much less is known about such detrimental copper effects in other organs. We therefore assessed the mitochondrial sensitivity to copper in a tissue specific manner, namely of isolated rat liver, kidney, heart, and brain mitochondria. Brain mitochondria presented with exceptional copper sensitivity, as evidenced by a comparatively early membrane potential loss, profound structural changes already at low copper dose, and a dose-dependent reduced capacity to produce ATP. This sensitivity was likely due to a copper-dependent attack on free protein thiols and due to a decreased copper reactive defense system, as further evidenced in neuroblastoma SHSY5Y cells. In contrast, an increased production of reactive oxygen species was found to be a late-stage event, only occurring in destroyed mitochondria. We therefore propose mitochondrial protein thiols as major targets of mitochondrial copper toxicity.
Gesehen am 02.04.2020